The effect of a program based on the use of learning patterns in acquiring basic mathematical skills and developing the imaginative thinking skills of learning difficulties 4th graders - Nashaweih, Ameera Mohammad; Rayyan, Adel Atieh (Journal of Educational and Psychological Sciences, 2021)
This study aimed at investigating the effect of a program based on the use of the learning patterns in acquiring basic mathematical skills and developing the imaginative thinking skills of learning difficulties 4th graders, to achieve the objectives of the study, the researchers used the experimental method and semi-experimental design (Pre-test and post-test) for one group on a target sample of 43 students from the students with learning difficulties in the 4th grade registered in the Directorate of South Hebron for the academic year 2018/2019. The sample of female students was selected from 4 sections with a total of 22 female students, and from 5 sections with a total of 21 male students. The sample was studied in a program based on learning patterns that were prepared by the researcher. The analysis of the basic mathematical skills test and imaginative thinking in the pre and post applications using T- test and the analysis of ANCOVA test showed that there are statistically significant differences at the level of significance (0.05 ≥ α) between the two means of student marks in the test of basic mathematical skills and in the test of imaginative thinking between the pre-test and the post-test for the benefit of the post test, and according to gender for the benefit of female. The study recommended the use of learning patterns in the teaching of mathematics, providing the necessary sources for this and the need to include them in the teacher’s guide and the prescribed books.